Russian firewall screening tools for secured systems - A. M. Sadykov; R. R. Yamaletdinov; D. I. Sabirova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the work is to make the comparative analysis of the firewall tools for secure systems on the Russian market. The sharp increase in demand for products from domestic developers is associated with the need to abandon the use of foreign information security tools and transition to Russian analogues. Method. Systematization, description and analysis are used as research methods. In this work functional analysis will be carried out in relation to the following solutions: «Universal security gateway «UserGate», security complex «Continent 4», hardware and software complex «ViPNet xFirewall 5», «Firewall with Ideco UTM intrusion detection system». Result. For comparison of firewall tools the following parameters were chosen: functionality of firewalls as network equipment, as means of protection, possibility of clustering, compliance with FSTEC requirements. The analysis of firewall tools showed that the Russian market offers to users worthy analogues of foreign products. However in this solutions some functionality is missing, which indicates the insufficient maturity of the domestic market of firewalls. Conclusion. The choice decision should be dictated by the requirements of a particular organization, based on consumer requests for the functionality or stability of the firewall.